ROLE OF LAW PROTECTION OF RIGHTS NARAPIDANA IN CLASS IIA KARAWANG - Rahmatiani, Lusiana; Safarandes Asmara, Andes (International Journal of Psychosocial Rehabilitation, 2020)
Nowadays there are many problems that occur in social life, which eventually in socializing life there is an imbalance between expectations and reality, the inequality becomes a very complex dynamic in various fields of life causing a shortage of daily needs that are felt by the community covering many layers of both society layers of youth and society layers of the elderly. The emergence of life problems, especially from the economic field, ultimately brings losses to himself due to acts against the law. Hence, with the existence of unlawful acts lead to arrests in detention centers (detention centers) or more popularly known as prisons (correctional institutions). Talks about prisoners or prisoners are inseparable from the rights of prisoners who must be kept and given during their detention and as humans cannot be released from their human rights even though prisoners are limited in space and time. The study was conducted in Class IIA prison in Karawang. The purpose of this study is to describe how the role of legal protection of prisoners' rights in class IIA prison in Karawang. The research method used is a qualitative method with data collection, observation, interview and documentation techniques.